Seasonal variations of arrhythmias and their impact on mortality in cancer patients with health disparities: A propensity score adjusted machine learning analysis of over 100 million hospitalizations across 3 years - Park Jong Kun; Monlezun Dominique; Kim Jin Wan; Going James; Khalaf Shaden; Honan Kevin; Ali Abdelrahman; Liu Victor; Barout Ahmad; Boone David; Safavi-Naeini Payam; Koutroumpakis Efstratios; et al. (Sciendo, 2024)
Seasonal Variations of Arrhythmias and Their Impact on Mortality in Cancer Patients with Health Disparities: A Propensity Score Adjusted Machine Learning Analysis of over 100 Million Hospitalizations Across 3 Years